Risk of appendicitis after endoscopic full-thickness resection of lesions involving the appendiceal orifice: a retrospective analysis - Schmidbaur, Simone; Wannhoff, Andreas; Walter, Benjamin; Meier, Benjamin; Schäfer, Claus; Meining, Alexander; Caca, Karel (Endoscopy, 2020)
Background Conventional endoscopic resection of lesions affecting the appendiceal orifice is difficult. Endoscopic full-thickness resection (EFTR) is a novel technique in interventional endoscopy. As EFTR near the appendiceal orifice is associated with a subtotal appendectomy, it remains unclear whether the risk of developing appendicitis is increased. We conducted a retrospective analysis of lesions involving the appendiceal orifice treated by EFTR.Methods This was a multicenter retrospective analysis of patients (n = 50) treated with EFTR for lesions involving the appendiceal orifice between 2014 and 2019. The objective was to evaluate the occurrence of appendicitis.Results Acute appendicitis occurred in seven patients (14 %) during follow-up. Conservative treatment was sufficient in four cases, and three patients underwent appendectomy.Conclusions EFTR of lesions involving the appendiceal orifice may be associated with an imminent risk of developing appendicitis and a consecutive need for appendectomy. Patients should be informed about this specific risk prior to resection. It is unclear why some patients develop appendicitis while the majority remains asymptomatic.